Systemic video analysis of hamstring injury mechanism for professional athletes: sprint-type injuries occurring during the swing phase of the running cycle - Yüce, A.; Oto, O.; Misir, A. (Medicina dello Sport, 2022)
BACKGROUND Hamstring injuries significantly affect the performance of high-speed athletes such as football, rugby, and American football. One of the methods to determine an injury mechanism in detail is to examine the event and the posture of the athlete at the time of injury using video analysis method. There here is limited data on systematic video analysis of hamstring injuries in athletes. The purpose of this study was to analyze the posture of the body parts regarding the injury mechanism using a video analysis method in athletes who were exposed to a sprint-type hamstring injury at the time of injury.